2022
DOI: 10.5829/ije.2022.35.06c.04
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis on Behavior of Single Battered Pile in Sandy Soil Under Pullout Loading

Abstract: Batter piles are the piles driven in the soil at an inclination with the vertical to withstand oblique loads or large horizontal loads and have been widely used to support high buildings, offshore buildings, and bridges. These constructions are risky because of the exposure to moments and overturning resulting from winds, waves, and ship impact. A 3D FEA using PLAXIS 3D software was used to investigate the effect of several variables that affect the behavior of single batter piles under pull-out loads. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Como parte de los resultados habrá que resaltar que los datos obtenidos permiten generar una serie de gráficas para identificar la tendencia de mejora para el caso de estudio y ser utilizado de manera satisfactoria como prototipo en investigación y aplicaciones académicas. La mayor cantidad de investigaciones de esta índole ofrecen diagramas y gráficas con los datos obtenidos a partir de llevar a cabo las simulaciones, por ejemplo, [28] establece que la carga límite de extracción en un espécimen aumenta con el incremento de la relación de esbeltez y la densidad relativa. Por otro lado, como valor agregado se tiene la experiencia de [29], indicando que un parámetro importante en los desarrollos experimentales y por ende en las simulaciones, es la velocidad en la ejecución de las simulaciones con cada uno de los especímenes.…”
Section: Resultados Y Discusionesunclassified
“…Como parte de los resultados habrá que resaltar que los datos obtenidos permiten generar una serie de gráficas para identificar la tendencia de mejora para el caso de estudio y ser utilizado de manera satisfactoria como prototipo en investigación y aplicaciones académicas. La mayor cantidad de investigaciones de esta índole ofrecen diagramas y gráficas con los datos obtenidos a partir de llevar a cabo las simulaciones, por ejemplo, [28] establece que la carga límite de extracción en un espécimen aumenta con el incremento de la relación de esbeltez y la densidad relativa. Por otro lado, como valor agregado se tiene la experiencia de [29], indicando que un parámetro importante en los desarrollos experimentales y por ende en las simulaciones, es la velocidad en la ejecución de las simulaciones con cada uno de los especímenes.…”
Section: Resultados Y Discusionesunclassified
“…The results of the testing models revealed that the uplift pile capacity of SURP and DURP is much greater than that of a straight pile for all L/D pile ratios. Al-Tememy et al [16] used PLAXIS-3D software to examine a model of the steel pipe pile installed in dry sand. Based on the outcomes, the relative density of the sand has an influence on the peak resistance pullout load of vertical piles.…”
Section: Introductionmentioning
confidence: 99%
“…A dry or wet binder variable mix is mechanically combined with in situ natural soil to build columns for improved soil. This type of foundation, called a composite foundation crowned with a cushion layer, [11,[13][14][15] that indirectly carrying the foundation load and enhances the bearing capacity of soft ground. Hence the cushion's deformability depends on its characteristics.…”
mentioning
confidence: 99%